2022
DOI: 10.23736/s1973-9087.22.07404-4
|View full text |Cite
|
Sign up to set email alerts
|

New technologies promoting active upper limb rehabilitation after stroke: an overview and network meta-analysis

Abstract: INTRODUCTION The primary aim of this work was to summarize and compare the effects of active rehabilitation assisted by new technologies (virtual reality [VR], robot-assisted therapy [RAT] and telerehabilitation [TR)) on upper limb motor function and everyday living activity during the subacute and chronic phases of stroke. The secondary aims were to compare the effects of these technologies according to the intervention design (in addition to or in substitution of conventional therapy), the durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 66 publications
0
22
0
Order By: Relevance
“…A recent review article introduced several studies using VR for upper limb rehabilitation in stroke patients, since it is a promising tool for encouraging active engagement of participants to lead to good outcomes [41]. However, one study showed only low to moderate results of VR techniques in subacute stroke patients [42]. Our results indicate not only positive effects of the RAPAEL ® Smart Glove digital system on upper limb function, but also possible evidence for underlying cortical hemodynamic changes detected by fNIRS.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…A recent review article introduced several studies using VR for upper limb rehabilitation in stroke patients, since it is a promising tool for encouraging active engagement of participants to lead to good outcomes [41]. However, one study showed only low to moderate results of VR techniques in subacute stroke patients [42]. Our results indicate not only positive effects of the RAPAEL ® Smart Glove digital system on upper limb function, but also possible evidence for underlying cortical hemodynamic changes detected by fNIRS.…”
Section: Discussionmentioning
confidence: 63%
“…In a previous study, robot-assisted therapy showed a comparable effect to conventional therapy, while VR showed no superiority to conventional therapy when provided alone [42]. However, both new techniques showed significantly better functional improvement when they were added to conventional therapy [18,42,43]. The RAPAEL ® Smart Glove digital system collects haptic data from a human body and provides real-time ROM information.…”
Section: Discussionmentioning
confidence: 99%
“…In another recent study, researchers aimed to summarize and compare the effects of active rehabilitation assisted by new technologies (virtual reality, robot-assisted therapy and tele-rehabilitation) on upper limb function during the subacute and chronic phases of stroke (30). 15 meta-analyses were based on 189 randomized controlled trials, were included in the quantitative analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In the neurorehabilitation approach, technology-based rehabilitation (TBR) merged as a clinical modality that provides new opportunities to enhance motor recovery after stroke [ 22 , 23 ]. Indeed, the last literature overviews confirm that the use of technological solutions, such as virtual reality or robotic devices, have shown encouraging results regarding motor recovery in stroke survivors.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the last literature overviews confirm that the use of technological solutions, such as virtual reality or robotic devices, have shown encouraging results regarding motor recovery in stroke survivors. However, there is a lack of evidence to support which approach is better [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%